(untitled) (mathematica didactica, 2024)
At the beginning of a preparatory course at the University of Münster, we surveyed cognitive and affective characteristics of prospective students in different mathematics degree programs. For cognitive characteristics, strengths emerged for mathematics majors and weaknesses for prospective elementary teacher students. For affective characteristics (interest, self-efficacy, and self-regulation), mathematics majors showed weaknesses in self-regulation and strengths in interest. Higher scores for self-regulation were found among student teachers. Based on the students’ cognitive and affective characteristics, different group profiles for different degree programs are identified.